Actuated signal setting design for an isolated intersection - Maharjan, Prajwal; Ampol Karoonsoontawong; Kunnawee Kanitpong; Surachet Pravinvongvuth (Pathum Thani : Asian Institute of Technology, 2016)
In a roadway intersection, traffic movements from different approaches lead to confusion and conflicts in traffic flow which causes congestion, delay and loss of valuable. For a uninterrupted passage of incoming and outgoing vehicles in an intersection traffic signals need to be installed. In this capstone project, an actuated signal timing was designed in order to improve mobility and reduce traffic flow conflicts. . An isolated intersection was designed with actuated signal control considering the traffic demands and geometry of the intersection. A signal phase plan was developed, appropriate detector placement, yellow and red time intervals and minimum and maximum green times for safe passage of vehicles and pedestrians were calculated. In this project, both full-actuated and semi-actuated signal control timings were developed.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Civil And Infrastructure Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2016
Keywords: Traffic signs and signals -- Thailand; Electronic traffic controls -- Thailand; Signalized intersections -- Thailand